The Role of Career Training to Enhance Career Planning - Nur Affifah, Yans; Khwarizmi, Muhammad Raja (Universitas Muhammadiyah Malang, 2024)
This research aims to determine and analyze the influence of career training in planning a career in the future. This research was conducted on all career training participants organized by the career center of the Faculty of Economics and Business, University of Muhammadiyah Malang in collaboration with CAKAP and Schoter. Respondents were all career training participants who attended 5 full training sessions totaling 147 people, but from the data collected only 100 met the requirements. The analytical tool used is multiple regression with SPSS 21. The results of the research show that career training has an influence on participants' career planning, but partially trainers and training modules have an influence on final planning, while training methods have no effect on final planning.